Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s40271-021-00524-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Through 1 Year of an HIV-1 Clinical Trial Evaluating Long-Acting Cabotegravir and Rilpivirine Administered Every 4 or 8 Weeks (ATLAS-2M)

Abstract: Background Advances in HIV-1 therapeutics have led to the development of a range of daily oral treatment regimens, which share similar high efficacy rates. Consequently, more emphasis is being placed upon the individual's experience of treatment and impact on quality of life. The first long-acting injectable antiretroviral therapy for HIV-1 (long-acting cabotegravir + rilpivirine [CAB + RPV LA]) may address challenges associated with oral treatment for HIV-1, such as stigma, pill burden/fatigue, drug-food inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Notably, participants were more satisfied with the regimens that they chose to receive in POLAR (both CABþRPV long-acting and oral DTG/RPV) than with the daily oral CABþRPV regimen they had previously received for at least 5 years, as measured by the HIVTSQc. In addition, 88% (n ¼ 77/88) of CABþRPV long-acting respondents stated a preference for CABþRPV longacting over their prior oral regimen, consistent with findings from the other Phase 3 studies (ATLAS, FLAIR, and ATLAS-2 M) evaluating CABþRPV long-acting [17][18][19][29][30][31]. Taken together, these results demonstrate high levels of preference for, and satisfaction with, the injectable regimen.…”
Section: Discussionsupporting
confidence: 81%
“…Notably, participants were more satisfied with the regimens that they chose to receive in POLAR (both CABþRPV long-acting and oral DTG/RPV) than with the daily oral CABþRPV regimen they had previously received for at least 5 years, as measured by the HIVTSQc. In addition, 88% (n ¼ 77/88) of CABþRPV long-acting respondents stated a preference for CABþRPV longacting over their prior oral regimen, consistent with findings from the other Phase 3 studies (ATLAS, FLAIR, and ATLAS-2 M) evaluating CABþRPV long-acting [17][18][19][29][30][31]. Taken together, these results demonstrate high levels of preference for, and satisfaction with, the injectable regimen.…”
Section: Discussionsupporting
confidence: 81%
“…While participant satisfaction with long-acting ART has been largely positive [ 2 ▪ , 25 28 ], provider enthusiasm has been more cautious. Concerns include the need for patients to adhere to injection visits for treatment to be successful [ 26 ].…”
Section: Cabotegravir and Rilpivirine For The Treatment Of Hivmentioning
confidence: 99%
“…Furthermore, the frequency of darbepoetin alfa administration and dosage changed from once every two weeks to once every four weeks when Hb levels were considered stable. A clinical trial focused on treatment satisfaction for people living with HIV and requiring long-term treatment management found that patient's preferred less frequent treatment and concluded that mode of administration is one characteristic that accounts for improved treatment satisfaction [20].…”
Section: Discussionmentioning
confidence: 99%